Different red light requirements for phytochrome-induced accumulation of cab RNA and rbcS RNA - Kaufman, L S; Thompson, W F; Briggs, W R (Science (American Association for the Advancement of Science), 1984)
For several species of plants the abundance of those transcripts encoding the chlorophyll a/b binding protein (cab RNA) and the small subunit of ribulose-1,5-biphosphate carboxylase-oxygenase (rbcS RNA) has been established as being under the control of phytochrome. However, this conclusion does not take into account the various types of phytochrome control based on both the fluence of red light necessary to induce the response and the ability of far red light either to induce or to reverse the response. The fluence of red light necessary to induce the accumulation of rbcS RNA was found to be 10,000 times greater than that necessary to induce the accumulation of cab RNA. Furthermore, far red light alone was capable of inducing the accumulation of cab RNA. It is possible, therefore, that developing pea buds accumulate cab RNA before rbcS and that cab RNA is not subject to the normal end-of-day signals affecting many phytochrome responses.